The label free picomolar detection of insulin in blood serum. - Xu, M; Luo, X; Davis, J (2013)
Insulin, a polypeptide hormone secreted by pancreatic cells, is a key regulator in glucose homeostasis. Its deficiency leads to insulin-dependent (type I) diabetes whereas resistance to insulin is common in type II diabetes, obesity and a range of endocrine disorders. Its determination is of considerable value, particularly in the clinical diagnosis of diabetes mellitus and the doping control of athletes. It has, additionally, been noted as a potential breast cancer marker (serum insulin levels being found to be raised in comparison to control patients). Electrochemical assays are potentially very cheap, highly sensitive, and very readily transposed to a point of care. Though there exist numerous examples of label free impedimetric or capacitative assaying of biomolecules, these are rarely demonstrated to be effective in complex biological mixtures or to be applicable to low molecular weight targets (since they operate through the interfacial displacement of water/ions and/or the steric blocking of a redox probe). We report herein an ultrasensitive electrochemical and label-free biosensor for insulin in blood serum with a clinically relevant linear range and detection limit of 1.2pM. The transducing surfaces, based on readily prepared, antibody modified, polyethylene glycol monolayer modified polycrystalline gold surfaces, respond in a highly specific and re-useable manner to the target in up to 50% blood serum.